A Novel Dynamic Morphed Stimuli Set to Assess Sensitivity to Identity and Emotion Attributes in Faces - Darke, Hayley; Cropper, Simon J.; Carter, Olivia (Frontiers in Psychology, 2019)
Face-based tasks are used ubiquitously in the study of human perception and cognition. Video-based (dynamic) face stimuli are increasingly utilised by researchers because they have higher ecological validity than static images. However, there are few ready-to-use dynamic stimulus sets currently available to researchers. This paper outlines the development of three original dynamic stimulus sets: a set of emotional faces (fear and disgust), a set of non-emotional faces, and a set of car animations. Morphing software was employed to vary the intensity of the expression shown and to vary the similarity between actors. These stimuli were then used to create experiments that are matched on task parameters and are highly sensitive to individual differences in performance. Methods for five example experiments are also included along with data from two experiments of the tasks in an experimental context. The data obtained from Experiment 1 demonstrated that the dynamic stimuli are suitable across a range of participants, successfully avoiding floor and ceiling effects. Experiment 2 revealed that dynamic versions of these stimuli were recognised more accurately than static versions, both for discrimination and labelling task paradigms. These stimuli therefore provide a useful resource for researchers looking to investigate emotion-processing using more sensitive and ecologically valid tools.